Estrogen and progesterone receptor testing in breast carcinoma: concordance of results between local and reference laboratories in Brazil - Wludarski, Sheila Cristina Lordelo (2011)
CONTEXT AND OBJECTIVE: Breast cancer accounts for approximately one quarter of all cancers in females. Estrogen and progesterone receptor testing has become an essential part of the clinical evaluation of breast carcinoma patients, and accurate results are critical in identifying patients who may benefit from hormone therapy. The present study had the aim of investigating the concordance of the results from hormone receptor tests between a reference laboratory and local (or community) laboratories in Brazil. DESIGN AND SETTING: Retrospective study at a reference pathology laboratory. METHODS: The concordance in the results from hormone receptor tests between a reference laboratory and 146 local laboratories in Brazil was compared in relation to 500 invasive breast carcinoma cases, using immunohistochemistry. RESULTS: There was concordance in 89.4% (447/500 cases) and 85.0% (425/500 cases) of the results from estrogen (k = 0.744, P < 0.001) and progesterone (k = 0.688, P < 0.001) receptor tests, respectively, between local and reference laboratories. This was similar to findings in other countries. The false negative rates from estrogen and progesterone receptor tests in local laboratories were 8.7% and 14.4%, respectively. The false positive rates from estrogen and progesterone receptor tests in local laboratories were 15.5% and 16.0%, respectively. CONCLUSION: Technical and result interpretation issues may explain most of the discordances in hormone receptor testing in local laboratories. Validation of estrogen and progesterone receptor tests at local laboratories, with rigorous quality control measures, is strongly recommended in order to avoid erroneous treatment of breast cancer patients.